Come rain or come shine - Karon, Jan, 1937- (New York : G. P. Putnam's Sons, an imprint of Penguin Random House LLC, 2015)
Graduating from vet school and opening an animal clinic, Dooley Kavanagh, Father Tim Kavanaugh's adopted son, plans what he hopes will be a simple, affordable wedding with soulmate Lace Harper.
Keywords: Mitford (N.C. : Imaginary place) -- Fiction; Weddings -- Fiction; Christian fiction